Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the expression [tex]\((2x - 5y)^3 - (2x + 5y)^3\)[/tex], let's follow these steps.
1. Understand the expression: We are dealing with a subtraction of two cubes:
[tex]\[ (2x - 5y)^3 - (2x + 5y)^3 \][/tex]
2. Use the algebraic identity for the difference of cubes: The difference of two cubes [tex]\(a^3 - b^3\)[/tex] can be factored using the identity:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
Here, [tex]\(a = 2x - 5y\)[/tex] and [tex]\(b = 2x + 5y\)[/tex].
3. Substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into the identity:
[tex]\[ (2x - 5y)^3 - (2x + 5y)^3 = [(2x - 5y) - (2x + 5y)][(2x - 5y)^2 + (2x - 5y)(2x + 5y) + (2x + 5y)^2] \][/tex]
4. Simplify the first binomial:
[tex]\[ (2x - 5y) - (2x + 5y) = 2x - 5y - 2x - 5y = -10y \][/tex]
5. Simplify the second part:
[tex]\[ (2x - 5y)^2 = 4x^2 - 20xy + 25y^2 \][/tex]
[tex]\[ (2x - 5y)(2x + 5y) = 4x^2 - 25y^2 \][/tex]
[tex]\[ (2x + 5y)^2 = 4x^2 + 20xy + 25y^2 \][/tex]
6. Combine these results:
[tex]\[ (2x - 5y)^2 + (2x - 5y)(2x + 5y) + (2x + 5y)^2 = 4x^2 - 20xy + 25y^2 + 4x^2 - 25y^2 + 4x^2 + 20xy + 25y^2 \][/tex]
7. Simplify the combination of terms:
[tex]\[ 4x^2 - 20xy + 25y^2 + 4x^2 - 25y^2 + 4x^2 + 20xy + 25y^2 = 4x^2 + 4x^2 + 4x^2 + 25y^2 - 25y^2 + 25y^2 = 12x^2 + 25y^2 \][/tex]
8. Multiply the simplified factors:
[tex]\[ -10y \cdot (12x^2 + 25y^2) = -10y \cdot 12x^2 - 10y \cdot 25y^2 = -120x^2y - 250y^3 \][/tex]
Hence, the final result of the given expression [tex]\((2x - 5y)^3 - (2x + 5y)^3\)[/tex] is:
[tex]\[ -120x^2y - 250y^3 \][/tex]
1. Understand the expression: We are dealing with a subtraction of two cubes:
[tex]\[ (2x - 5y)^3 - (2x + 5y)^3 \][/tex]
2. Use the algebraic identity for the difference of cubes: The difference of two cubes [tex]\(a^3 - b^3\)[/tex] can be factored using the identity:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
Here, [tex]\(a = 2x - 5y\)[/tex] and [tex]\(b = 2x + 5y\)[/tex].
3. Substitute [tex]\(a\)[/tex] and [tex]\(b\)[/tex] into the identity:
[tex]\[ (2x - 5y)^3 - (2x + 5y)^3 = [(2x - 5y) - (2x + 5y)][(2x - 5y)^2 + (2x - 5y)(2x + 5y) + (2x + 5y)^2] \][/tex]
4. Simplify the first binomial:
[tex]\[ (2x - 5y) - (2x + 5y) = 2x - 5y - 2x - 5y = -10y \][/tex]
5. Simplify the second part:
[tex]\[ (2x - 5y)^2 = 4x^2 - 20xy + 25y^2 \][/tex]
[tex]\[ (2x - 5y)(2x + 5y) = 4x^2 - 25y^2 \][/tex]
[tex]\[ (2x + 5y)^2 = 4x^2 + 20xy + 25y^2 \][/tex]
6. Combine these results:
[tex]\[ (2x - 5y)^2 + (2x - 5y)(2x + 5y) + (2x + 5y)^2 = 4x^2 - 20xy + 25y^2 + 4x^2 - 25y^2 + 4x^2 + 20xy + 25y^2 \][/tex]
7. Simplify the combination of terms:
[tex]\[ 4x^2 - 20xy + 25y^2 + 4x^2 - 25y^2 + 4x^2 + 20xy + 25y^2 = 4x^2 + 4x^2 + 4x^2 + 25y^2 - 25y^2 + 25y^2 = 12x^2 + 25y^2 \][/tex]
8. Multiply the simplified factors:
[tex]\[ -10y \cdot (12x^2 + 25y^2) = -10y \cdot 12x^2 - 10y \cdot 25y^2 = -120x^2y - 250y^3 \][/tex]
Hence, the final result of the given expression [tex]\((2x - 5y)^3 - (2x + 5y)^3\)[/tex] is:
[tex]\[ -120x^2y - 250y^3 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.